The evolution of digital competence in pre-service teachers: a global perspective from 2009-2024 - An Bien Thuy; Ha Van Dung; Nguyen Thi Lan-Ngoc; Pham Thi Hong-Hanh; Nguyen Thi Viet-Nga; Trinh Thi Phuong Thao (International Journal of Evaluation and Research in Education (IJERE), 2026)
In the context of the strong digital transformation occurring in education, digital competence (DC) is one of the essential skills for pre-service teachers. Therefore, equipping students in teacher training programs with DC is a significant public concern. This study analyzes global research output on pre-service teachers’ DC to identify publication trends, key contributors, and predominant research themes. To gain a comprehensive view of pre-service teachers’ DC, the research team conducted a bibliometric analysis of 278 publications from the Scopus database, from 2009 to 2024. The results reveal a substantial increase in publications on DC in pre-service teachers, particularly in the last 3 years. Spain is a leading country in this collection, with the most publications and funding mentions. The most prominent author is Çebi from Turkey. The journal that published the most articles is Education and Information Technologies (EAIT). Through the analysis of co-occurring keywords, four main research trends on this topic have been identified. The findings of this study provide valuable insights into the research topic and contribute to shaping future research directions in this field.